2020
DOI: 10.1038/s41598-020-65712-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of rGO-PEI/Naph-SH/AgNWs/Frt/GOx nanocomposite anode for biofuel cell applications

Abstract: The present study reports a new nanocomposite design using surface modified silver nanowires decorated on the surface of polyethyleneimine (PEI), a cationic polymer acting as glue for anchoring nanowires and reduced graphene oxide (rGo). the synthesized nanocomposite was employed as a promising electrode material for immobilization of biomolecules and effective transportation of electron, in enzymatic biofuel cell (EBFCs) application. The synthesized nanocomposite was confirmed by analytical techniques, for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Different from PANI and PPy with outstanding conductivity, PEI is a biocompatible porous cationic polymer with many advantages such as ease of preparation and exceptional enzyme immobilizing ability. 122 Kwon et al 123 applied PEI as an amine axial ligand to coordinate with the Co core within cobalt phthalocyanine and composite with graphene ([RGO/CoPc]/PEI), and the resulting composite displays good performance for hydrogen peroxide oxidation. Hence, they utilized this composite as the support for GOx immobilization to remove the unwanted H 2 O 2 during oxidation reactions, and the obtained glucose EBFC delivered a maximum power output of 25.4 AE 0.9 mW cm À2 .…”
Section: Carbon-polymer Compositesmentioning
confidence: 99%
“…Different from PANI and PPy with outstanding conductivity, PEI is a biocompatible porous cationic polymer with many advantages such as ease of preparation and exceptional enzyme immobilizing ability. 122 Kwon et al 123 applied PEI as an amine axial ligand to coordinate with the Co core within cobalt phthalocyanine and composite with graphene ([RGO/CoPc]/PEI), and the resulting composite displays good performance for hydrogen peroxide oxidation. Hence, they utilized this composite as the support for GOx immobilization to remove the unwanted H 2 O 2 during oxidation reactions, and the obtained glucose EBFC delivered a maximum power output of 25.4 AE 0.9 mW cm À2 .…”
Section: Carbon-polymer Compositesmentioning
confidence: 99%
“…However, the barrier leading to low DET is that the redox center found in the enzyme is located deeply in 3D protein matrices [15,28]. Among the ways to increase electron transfer through MET and DET is to use small molecules of the active mediators and develop highly conductive materials with a high active site for enzyme loading, respectively [56]. Herkendell et al [57] created a double layer of carbon electrode in which the mesoporous carbon nanoparticle and carbon-coated magnetic nanoparticle, referring to the first and second layers of carbon electrode, activated both MET and DET, respectively.…”
Section: The Enzyme Support and Substrate In Ebfcmentioning
confidence: 99%
“…A high current density of 4.9 mA/cm 2 produced after consuming 50 mM glucose concentration proves an electron transfer that applies efficiently. The same group's research using nickel oxide and silver nanowires showed a higher current density of 5.4 [16] and 19.9 mA/cm 2 [56]. Investigations that use CNT as support material have been carried out widely in EBFC.…”
Section: Current Development On the Bioanode And Biocathode In Ebfcmentioning
confidence: 99%
“…The oxygen evolution reaction (OER) has received much interest as a result of its critical role in a variety of energy storage and conversion applications, which include water splitting, rechargeable metal–air batteries, and regenerative fuel cells. The oxygen evolution process is kinetically sluggish, and significantly high overpotentials are required to drive the reactions. Currently, RuO 2 and IrO 2 catalysts are the best OER catalysts for commercial use. However, the scarcity of Ru and Ir catalysts has made these catalysts less attractive for the development of commercial devices. , In this regard, the metal oxides, which are abundant in the Earth’s crust, are studied extensively as an alternative material for the desired OER catalysts performance. , However, the low conductivity of these materials restricted the OER performance. There are efforts to improve the conductivity by the addition of conductive carbon-based materials in metal oxide compounds, but the oxidation of carbon during an electrochemical cycle is still a challenge. , …”
Section: Introductionmentioning
confidence: 99%